2015
DOI: 10.4103/2454-6798.165115
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of doctors toward euthanasia in Delhi, India

Abstract: Introduction: Deliberation over euthanasia has been enduring for an extended period of time. On one end, there are populaces talking for the sacrosanctity of life and on the other end, there are those, who promote individual independence. All over the world professionals from different areas have already spent mammoth period over the subject. A large number of cases around the world have explored the boundaries of current legal distinctions, drawn between legitimate and nonlegitimate instances of ending the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
2
7
1
Order By: Relevance
“…These findings indicate the daily dilemmas physicians face when on the one hand, they are committed to protecting the sanctity of life, and yet, on the other hand, they are committed to alleviating the patient’s suffering while respecting their autonomy and choice. We found no differences between men and women regarding attitudes toward euthanasia which is in line with other studies [ 21 , 22 ]. As for the positive relationship between seniority and attitudes toward euthanasia, previous studies have found that euthanasia is more favorable among older, veteran physicians who have had previous encounters with terminal patients and are more likely to provide patients with lethal drugs if asked to by terminal patients seeking to end their lives [ 21 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings indicate the daily dilemmas physicians face when on the one hand, they are committed to protecting the sanctity of life, and yet, on the other hand, they are committed to alleviating the patient’s suffering while respecting their autonomy and choice. We found no differences between men and women regarding attitudes toward euthanasia which is in line with other studies [ 21 , 22 ]. As for the positive relationship between seniority and attitudes toward euthanasia, previous studies have found that euthanasia is more favorable among older, veteran physicians who have had previous encounters with terminal patients and are more likely to provide patients with lethal drugs if asked to by terminal patients seeking to end their lives [ 21 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…These ndings indicate the dilemmas physicians face, when on the one hand, they are committed to protecting the sanctity of life, and yet, on the other hand, they are interested in alleviating the patient's suffering while respecting their autonomy and choice. We found no signi cant differences between men and women regarding attitudes toward euthanasia which is in line with other studies (21,22). As for the positive relationship between seniority and attitudes toward euthanasia, previous studies have found that euthanasia is more favorable among older, veteran physicians who have had previous encounters with terminal patients, and are more likely to provide patients with lethal drugs if asked to by terminal patients seeking to end their lives (21,23).…”
Section: Respondent Demographicssupporting
confidence: 91%
“…In context to advanced medical directive (AMD), previously a study conducted in India reported that 60% of the doctors and 59% of the nurses had a view that 'there should be some legal avenue where the patient can pre-authorize his/her death'. 8 However, in the present study, there was lack of awareness among the health professionals about AMD.…”
Section: Discussioncontrasting
confidence: 55%
“…5,10 However, on the contrary, one of the study did not support euthanasia and considered it as unethical since we are emotional and care driven society and probably it is still considered a taboo to discuss death and end of life. 8 Also, the fear of its misuse is high due to 'rampant corruption and mass commercialization' as quoted by supreme court of India. Majority (65.3%) of the participants perceived that AD and VE is helping a person with a terminal illness to die.…”
Section: Discussionmentioning
confidence: 99%